Collaborative Research (CR): To reduce transaction cost in open innovation - Porath, Amiram (2015)
As a conceptual study this paper takes open innovation as a tool that has been considered from the point of view of collaboration between the Industry and the Academy. However, if considered under the framework of the Resource Based Theory, specifically regarding Transaction Cost, it can be revealed that the two parties (Industry and Academy) are in fact compatible. Main focus of the discussion is on the Transaction Cost in the aspect of the management resources that are available for managing core activities and the cost incurred compared to other alternative management activities. It has been observed that small and medium enterprises (SMEs) are faced with the ever increasing stress of intensive competition and limited by their resources (for example, managerial capabilities, financial, and others) in their abilities to deal with the transaction cost, and thus effectively turn to collaboration as a solution. The study synthesizes aspects of open innovation based on a theoretical model and a case study of the User Association of Advanced Technologies program in Israel, and emphasizes on collaboration as an open innovation activity within the Resource Based Theory. Thereafter, it concludes that collaborative research reduced the transaction cost in terms of utilizing open innovation in entrepreneurships, especially in case of SMEs, before providing a few research hints. The research piggybacks on the acquired knowledge on open innovation and thus strengthens further the concept of reduction of transaction cost through collaborative research based on the specific case study.